Pengaruh Audit Fee, Audit Tenure dan Profitabilitas Terhadap Kualitas Audit dengan Komite Audit sebagai Variabel Moderasi - Meilie Ratanacitta Exeliem; Hermie Hermie (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effects of audit fee , audit tenure, and profitability on audit quality, with the audit committee as a moderating variable in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research employs a quantitative approach using secondary data obtained from companies’ annual reports. The sample was selected using a purposive sampling method, resulting in 27 companies with a total of 135 observations. From the 135 observations, an outlier test was conducted, yielding 131 final observations used in the analysis. The data analysis methods applied include panel data regression and Moderated Regression Analysis (MRA) using SPSS software. The hypothesis testing results indicate that (1) audit fee has a negative effect on audit quality, (2) audit tenure has a positive effect on audit quality, (3) professional ethics has no effect on audit quality, (4) the audit committee does not weakens the negative effect of audit fee on audit quality, (5) the audit committee does not strengthen the positive effect of audit tenure on audit quality, and (6) the audit committee strengthen the positive effect of profitability on audit quality.